The State Of Health Of Malaysian Managers - ONG, JOO LEE (2004)
A healthy workforce is an essential element for Malaysia to achieve Vision 2020. However, there is a dearth of information on the state of health of Malaysian managers. The objective of this study, therefore, is to fill this gap by providing some baseline information on the issue and the salient lifestyle factors contributing to the level of physical and mental health of Malaysian managers.